Brain accumulation of amyloid β protein visualized by positron emission tomography and BF‐227 in Alzheimer's disease patients with or without diabetes mellitus. Issue 1 (10th June 2012) - Tomita, Naoki; Furukawa, Katsutoshi; Okamura, Nobuyuki; Tashiro, Manabu; Une, Kaori; Furumoto, Shozo; Iwata, Ren; Yanai, Kazuhiko; Kudo, Yukitsuka; Arai, Hiroyuki
Abstract : Aim:  Although diabetes mellitus (DM) is considered to be one of the most consistent risks for developing dementia, it is not known if the pathology in dementia patients with DM is similar to or distinct from typical pathological features of Alzheimer's disease (AD). To discover the mechanism of developing dementia in AD patients with DM in a living state, we studied the distribution of amyloid β (Αβ) protein of diabetic AD patients. Methods:  To evaluate the accumulation of Aβ, we examined 14 normal controls, four diabetic patients with AD and 11 non‐diabetic patients with AD by positron emission tomography (PET) using BF‐227, a currently developed Aβ tracer. Results:  The analysis of PET images among the three groups showed an abundant aggregated Aβ accumulation in the cerebral cortex of both AD patients with and without DM. The extent and distributions of BF‐227 accumulation in diabetic AD patients were not significantly different from these of non‐diabetic AD patients. Conclusion:  These results suggest that the degree and extent of Aβ deposition is not significantly different between AD with DM and AD alone.Geriatr Gerontol Int 2013; 13: 215–221.